2013
DOI: 10.1002/jgra.50145
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of magnetosheath flows and magnetopause shape during low Alfvén Mach number solar wind

Abstract: [1] Previous works have emphasized the significant influence of the solar wind Alfvén Mach number (M A ) on magnetospheric dynamics. Here we report statistical, observational results that pertain to changes in the magnetosheath flow distribution and magnetopause shape as a function of solar wind M A and interplanetary magnetic field (IMF) clock angle orientation. We use all Cluster 1 data in the magnetosheath during the period 2001-2010, using an appropriate spatial superposition procedure, to produce magnetos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 61 publications
8
52
0
Order By: Relevance
“…The analyses of MCs in many studies (e.g., Chané et al 2005;Dasso et al 2006Dasso et al , 2007Ruffenach et al 2012Ruffenach et al , 2015Lavraud et al 2013Lavraud et al , 2014 have revealed the predicted features of flux rope erosion. Dasso et al (2006) examined the 21 January 2005 ICME and found a large imbalance in B z that they attribute to magnetic reconnection.…”
Section: Flux Rope Erosionmentioning
confidence: 99%
“…The analyses of MCs in many studies (e.g., Chané et al 2005;Dasso et al 2006Dasso et al , 2007Ruffenach et al 2012Ruffenach et al , 2015Lavraud et al 2013Lavraud et al , 2014 have revealed the predicted features of flux rope erosion. Dasso et al (2006) examined the 21 January 2005 ICME and found a large imbalance in B z that they attribute to magnetic reconnection.…”
Section: Flux Rope Erosionmentioning
confidence: 99%
“…Observations indicate the presence of dawn-dusk asymmetries in the magnetosheath speed (Longmore et al, 2005;Walsh et al, 2012). The properties of the magnetosheath during low Alfvén Mach number (M A ) solar wind, corresponding to ICMEs and MCs conditions, have been investigated both observationally and numerically in Lavraud and Borovsky (2008) and Lavraud et al (2013). Their results show that the solar-windmagnetosphere coupling is altered in low M A conditions, and phenomena such as asymmetric and enhanced flows or asymmetric magnetopause compression are observed.…”
Section: Turc Et Al: Magnetosheath Model For Magnetic Cloudsmentioning
confidence: 99%
“…These accelerated flows are not due to reconnection but are rather the result of the draping of the interplanetary magnetic field (IMF) around the magnetosphere (e.g., Chen et al, 1993;Lavraud et al, 2007Lavraud et al, , 2013Rosenqvist et al, 2007;Petrinec at al., 1997;Lavraud and Borovsky, 2008;Harris, 2011). As explained below, a characteristic feature of these events, which is useful in their identification, is that the flow tends to be perpendicular to the local magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…We also carry out a statistical analysis to determine global features of these accelerations, with focus mainly on magnetosheath speeds that exceed the speed of the solar wind. A statistical survey of global magnetosheath speeds for speeds smaller than the solar wind is undertaken by Lavraud et al (2013).…”
Section: Introductionmentioning
confidence: 99%